PERKEMBANGAN PENDIDIKAN ISLAM MASA AWAL DI KALIMANTAN - Jeprianto Jeprianto; Bahaking Rama; Muhammad Rusdi Rasyid (CV. ADIBA AISHA AMIRA, 2023)
Islamic education in Kalimantan in its historical trajectory has its own pride, with the publication of a person who received the title